ENHANCING LANGUAGE LEARNING THROUGH REASONED IMITATION IN THE USE OF NUMERICAL RESOURCES IN THE FLE CLASSROOM - Hutapea, William Anderson; Jhoni Maslan; Marice (Esteem Journal of English Education Study Programme, 2025)
This study explores students' perspectives on the integration of artificial intelligence (AI) in the course Exploitation des Ressources Numériques en Classe du FLE, within the French Language Education Program at Universitas Negeri Medan. The course emphasizes the linguistic use of numerical and digital resources to support French as a Foreign Language (FLE) instruction. Using a descriptive quantitative method, data were collected from second-semester students via questionnaires. The findings show that students positively view AI as a language support tool, particularly in idea generation, text translation, and teaching material development. AI encourages reasoned imitation, where learners not only replicate but also critically adapt AI-generated content for language teaching purposes. However, students also expressed concerns about excessive dependence on AI, emphasizing the importance of critical thinking, ethical use, and the teacher’s role in guiding proper language application. Technical issues such as limited internet access and device availability were also reported. In conclusion, students demonstrate a constructive yet cautious attitude toward AI in language learning. The study highlights the need to promote responsible and reflective use of AI in exploiting numerical resources to enhance linguistic competence in FLE classrooms.